2019
DOI: 10.17509/factum.v8i1.20120
|View full text |Cite
|
Sign up to set email alerts
|

Rekam Jejak Pangeran Aria Soeria Atmadja (Bupati Sumedang Tahun 1883-1919)

Abstract: Pangeran Aria Soeria Atmadja was a Sumedang’s Regent figure who came from a royal family. When he became Sumedang’s Regent in 1883-1919, he received a lot of prizes from Netherland Colonial Government. This research highlighted the question, “How was the Role of Pangeran Aria Suriaatmadja as a Sumedang’s Regent in 1883-1919?”. During his leadership, Pangeran Aria Soeria Atmadja issued various policies to the Sumedang’s people, such as school development policy in the entire villages of Sumedang Regency, planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Pada masa pemerintahannya terjadi perkembangan pada segi ekonomi dan sosial masyarakat Sumedang. Ia memerintahkan pembangunan Sekolah Pertanian dan memperkenalkan teknologi terasering pada pesawahan di Sumedang (Handayani et al, 2019) (Lasmiyati, 2014). Pada tahun 1914, pemerintah kolonial dihadapkan masalah pecahnya Perang Dunia I di Eropa.…”
Section: Latar Sejarahunclassified
See 1 more Smart Citation
“…Pada masa pemerintahannya terjadi perkembangan pada segi ekonomi dan sosial masyarakat Sumedang. Ia memerintahkan pembangunan Sekolah Pertanian dan memperkenalkan teknologi terasering pada pesawahan di Sumedang (Handayani et al, 2019) (Lasmiyati, 2014). Pada tahun 1914, pemerintah kolonial dihadapkan masalah pecahnya Perang Dunia I di Eropa.…”
Section: Latar Sejarahunclassified
“…Pada tahun 1919, Pangeran Aria Suria Atmadja menyatakan pensiun dari jabatannya sebagai bupati Sumedang karena usia tua. Ia kemudian digantikan oleh adiknya yang bernama Raden Adipati Aria Kusumahdilaga (1919Kusumahdilaga ( -1937 (Handayani et al, 2019). Dengan lengsernya kekuasaan Pangeran Aria, pemerintah Kolonial tidak banyak khawatir karena penerusnya tidak memiliki niatan untuk mengancam kedudukan pemerintah Hindia Belanda.…”
Section: Fase Benteng Pertahananunclassified
“…Furthermore, it was found that there was an attempt to remove the influence of power from the previous regime, and that the story of Cadas Pangeran is a myth. Another study conducted by Handayani, Wiyanati & Yulifar (2019) found that Prince Aria Soeria Atmadja spent a lot of time studying general education, language and Islamic religious knowledge in Islamic boarding schools. In addition, all the policies he did were for the welfare of the people.…”
Section: Introductionmentioning
confidence: 99%